DIAGNOSIS AND TREATMENT OF NEW-ONSET MYASTHENIA GRAVIS IN CRITICALLY ILL PATIENTS - E. B. Vasilyeva; V. I. Kartavenko; S. S. Petrikov; S. A. Badygov; D. V. Sidnev; L. A. Savin (Неотложная медицинская помощь, 2016)
ABSTRACT. Myasthenia gravis is an autoimmune disease leading to weakness and pathological fatigue. The basis of the pathogenesis of myasthenia gravis is a disturbance of neurotransmission due to the influence of polyclonal autoantibodies on various structures of the neuromuscular junction. The recurrent or progressive course is common for the disease. It is extremely difficult to suspect and diagnose this pathology for an anesthesiologist-resuscitator who doesn’t treat patients with myasthenia gravis in everyday practice, since the patients often arrive to mainstream hospitals in critical condition with incorrect diagnosis. only specialized units of neurology have electromyographs and equipment for particular immunological probes. We report a case of myasthenia gravis in a patient admitted to a hospital emergency room with the other disease suspected.